EFEKTIVITAS PEMBELAJARAN MATEMATIKA MENGGUNAKAN MODEL PEMBELAJARAN MISSOURI MATEMATICS PROJECT (MMP) DENGAN METODE TALKING STICK DAN PENEMUAN TERBIMBING - supratman 89 Ellang; La Ode Sirad (De Fermat : Jurnal Pendidikan Matematika, 2021)
This research is an experimental study with the aim of knowing the effectiveness of the application of the Missouri Mathematics Project (MMP) learning model using the talking stick method and guided discovery. The hypothesis in this study is that the students' mathematics learning outcomes using the Missouri Mathematics Project (MMP) learning method using the talking stick method and guided discovery are more effective than conventional learning models in Class VIII students of SMP Negeri 1 Kolaka. The population in this study were all students of class VIII with a total of 275 people. Sampling was done by random cluster so that selected sample is 2 classes, namely VIIIA and VIIIC. Data were collected by means of learning outcomes tests. The results of inferential research using the t-test have obtained a significant value = 0.036 <α = 0.05, indicating that H0 is rejected and H1 is accepted. This inferential means that there is a significant difference between the mathematics learning outcomes of students taught by the Missouri Mathematics Project (MMP) learning model with the talking stick method and guided discovery and conventional learning models in Class VIII students of SMP Negeri 1 Kolaka. From the results of these studies, it can be concluded that the mathematics learning outcomes of students with the application of the Missouri Mathematics Project (MMP) learning model with the talking stick method and guided discovery are more effective than the conventional learning model in Class VIII students of SMP Negeri 1 Kolaka.